2009
DOI: 10.1159/000251961
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ccdc33, </i>a Predominantly Testis-Expressed Gene, Encodes a Putative Peroxisomal Protein

Abstract: Many genes crucial for male fertility are often predominantly or exclusively expressed in male germ cells. The analysis of mouse models has demonstrated the functional importance of peroxisomes in spermatogenesis. The CCDC33 protein has been reported to be a cancer/testis (CT) antigen. We found that mouse Ccdc33 is predominantly expressed in the testis and undergoes alternative splicing to produce at least 4 different transcripts. The protein encoded by Ccdc33 contains 3 coiled-coil domains, a C2-domain, 2 ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 103 publications
1
12
0
Order By: Relevance
“…As reported for brain in this review, recent studies in lung and testis also showed that the peroxisomal proteome in these tissues diverges significantly from the well-characterized liver and kidney peroxisomes (Karnati and Baumgart-Vogt 2009; Dastig et al 2011). In this respect, the continuous identification of novel tissue-specific peroxisomal proteins (Grzmil et al 2007;Kaczmarek et al 2009) will result in fascinating functional discoveries. Although our knowledge on peroxisome biogenesis has become increasingly detailed through recent years, many mysteries regarding the functional characterization and physiological role of peroxisomes lay ahead awaiting to be deciphered.…”
Section: Discussionmentioning
confidence: 53%
“…As reported for brain in this review, recent studies in lung and testis also showed that the peroxisomal proteome in these tissues diverges significantly from the well-characterized liver and kidney peroxisomes (Karnati and Baumgart-Vogt 2009; Dastig et al 2011). In this respect, the continuous identification of novel tissue-specific peroxisomal proteins (Grzmil et al 2007;Kaczmarek et al 2009) will result in fascinating functional discoveries. Although our knowledge on peroxisome biogenesis has become increasingly detailed through recent years, many mysteries regarding the functional characterization and physiological role of peroxisomes lay ahead awaiting to be deciphered.…”
Section: Discussionmentioning
confidence: 53%
“…That progressive loss of male fertility might be a conserved feature of peroxisomal biogenesis disorders is suggested by observations in Drosophila models (75), as well as in knock-out mice for peroxisomal multifunctional protein 2 (76). The relevance of peroxisomes in spermatogenesis is additionally illustrated by the existence of the male-germ-cell-specific peroxisomal proteins PXT1 (77) and CCDC33 (78), the expression of which starts at the spermatocyte stage. In view of that, it was proposed that instead of being degraded, peroxisomes might remodel their proteome during spermatogenesis to acquire new functions (68).…”
Section: Discussionmentioning
confidence: 99%
“…Transfection was performed, as described (Grzmil et al, 2007; Kaczmarek et al, 2009), with 1 μg (for single transfection) or 2 × 0.5 μg (for cotransfection) of construct(s) DNA. After 24 h of transient transfection, the cells were fixed with 4% paraformaldehyde and 0.1% Tween 20 for 15 min at RT.…”
Section: Methodsmentioning
confidence: 99%